The impact of work–family conflict on occupational fatigue among endoscopy nurses in China: a moderated mediation model - Zeng, Zhi; Zhou, Sumei; Liu, Meng; Xie, Guiqiong; He, Yazhi; Zhang, Jiquan (Frontiers in Public Health, 2024)
Background: Endoscopy nurses in China face significant work-family conflicts, where the clash between high work demands and family responsibilities markedly increases the risk of occupational fatigue. This not only affects the nurses' physical and mental health and overall well-being, but also poses a threat to the quality of care and patient safety. This study, grounded in the Conservation of Resources theory, constructs a moderated mediation model to examine the mediating role of positive coping style in the relationship between work-family conflict and occupational fatigue among endoscopy nurses in China, as well as the moderating effect of perceived social support. Methods A convenience sampling method was employed to select 315 endoscopy nurses from 25 tertiary hospitals across 14 provinces in China. A questionnaire survey was conducted using the Fatigue Assessment Instrument, the Work-Family Conflict Scale, the Simplified Coping Style Questionnaire, and the Perceived Social Support Scale. The moderated mediation model was validated using Stata16.0. Results Our findings reveal that work-family conflict is a significant predictor of occupational fatigue, with a negative impact on positive coping style. Positive coping style, in turn, is negatively associated with occupational fatigue. Furthermore, positive coping style partially mediates the relationship between work-family conflict and occupational fatigue, accounting for 35.52% of the total effect. Additionally, perceived social support mitigates the negative effects of work-family conflict on positive coping style and occupational fatigue. Conclusion There exists a moderated mediation effect between work-family conflict and occupational fatigue among endoscopy nurses in China, wherein positive coping style serve as a mediating variable. Perceived social support mitigates the negative impact of work-family conflict on positive coping style, while enhancing the alleviating effect of positive coping style on occupational fatigue. Therefore, improving endoscopy nurses' levels of perceived social support and coping strategies may help to prevent and alleviate the occurrence of occupational fatigue.